Combined de novo transcriptomic and physiological analyses reveal RyALS3-mediated aluminum tolerance in Rhododendron yunnanense Franch - Xu, Yan-Xia; Lei, Yun-Sheng; Huang, Shan-Xia; Zhang, Jing; Wan, Zi-Yun; Zhu, Xiang-Tao; Jin, Song-Heng (Frontiers in Plant Science, 2022)
Rhododendron (Ericaceae) has not only ornamental value, but great medicinal and edible values. Many of Rhododendron species are native to acid soils where aluminum (Al) toxicity limits plant productivity and species distribution. However, it remains unknown how Rhododendron adapts to acid soils. Here, we investigated the physiological and molecular mechanisms of Al tolerance in Rhododendron yunnanense Franch. We found that the shoots of Rhododendron yunnanense Franch did not accumulate Al after exposure of seedlings to 50 μM Al for 7 days, but predominantly accumulated in roots, suggesting that root Al immobilization contributes to its high Al tolerance. Whole-genome de novo transcriptome analysis was carried out for Rhododendron yunnanense Franch root apex in response to 6 h of 50 μM Al stress. A total of 443,639 unigenes were identified, among which 1,354 and 3,413 were up- and down-regulated, respectively, by 6 h of 50 μM Al treatment. Both Gene Ontology (GO) enrichment and the kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analyses revealed that genes involved in “ribosome” and “cytoskeleton” are overrepresented. Additionally, we identified Al-tolerance homologous genes including a tonoplast-localized ABC transporter RyALS3;1. Overexpression of RyALS3;1 in tobacco plants confers transgenic plants higher Al tolerance. However, root Al content was not different between wild-type plants and transgenic plants, suggesting that RyALS3;1 is responsible for Al compartmentalization within vacuoles. Taken together, integrative transcriptome, physiological, and molecular analyses revealed that high Al tolerance in Rhododendron yunnanense Franch is associated with ALS3;1-mediated Al immobilization in roots.